Formação continuada em ensino híbrido, práticas pedagógicas inovadoras, possibilidades integrativas no ensino fundamental anos iniciais - Silva, Hellen Corrêa da (2023)
Many researches recognize the importance of access to scientific and technological knowledge from childhood, thus enabling the formation of more critical individuals capable of perceiving and acting in the world. Analyzing the historical context, some researchers sought innovative pedagogical practices and solutions that contribute to the development of the teaching and learning process and provide opportunities for a more pluralistic education. Others investigate how digital technologies can help both in teacher training and the process of learning, and how teaching strategies can stimulate students, with the aim of proposing educational approaches that innovate and encourage more creative, attractive and efficient teaching. Currently, Blended Learning has great prominence when it comes to new educational perspectives, combined with the use of digital technologies to promote personalized learning experiences. This study proposes to investigate how the adoption of innovative pedagogical practices with the use of digital technologies can enrich teaching-learning processes, so that they become more active, interactive and integrative in Elementary Education Early Years using the approach of Blended Teaching. We also sought to systematize and integrate these subjects in an Ausubelian perspective, linking meaningful learning with the cognitivist approach. This research has a qualitative and quantitative nature, supporting and developing the text with a theoretical-methodological approach. Investigating and analyzing teacher training aimed at implementing innovative pedagogical practices through a Blended Teaching course, aimed at teachers who are teaching science. It also explores some of the obstacles encountered in carrying out teaching that provides potentially meaningful and personalized experiences for Elementary School students, especially in the Early Years. It is expected to contribute to improving the quality of teaching, making it more active, personalized, interactive and integrative. With the potential for significant impact on education, as it can generate results and knowledge that can be applied by educators and professionals in the field. And finally, in new proposals for continuing training courses for teachers and the production of innovative educational materials, based on innovative pedagogical practices and digital technologies, that can be used by schools and educators across the country.